Efektivitas Penerapan Audit Kepatuhan Sistem Informasi Akuntansi Penerimaan Kas pada UMKM Roti Raos melalui Pengendalian Internal - Dhea Imroatul Fatihah; Trias Arimurti; Meliana Puspitasari; Nur Azizah (Journal of Management and Creative Business, 2026)
This study aims to analyze the internal control in the cash receipt accounting information system at Toko Roti Raos and the role of compliance audits in maintaining data integrity. In managing cash receipts, Toko Roti Raos requires a reliable accounting information system to ensure that all transactions are recorded correctly and transparently. Effective internal control is crucial to ensure that the cash receipt process runs smoothly without errors or potential fraud. This research uses a qualitative approach with a case study in the bakery industry. Data were collected through interviews with management, field observations, and document analysis related to the cash receipt accounting information system. The research findings indicate that Toko Roti Raos has implemented solid internal controls to ensure the smooth running of the cash receipt process. The applied compliance audit system functions to examine and assess adherence to existing procedures, thus reducing the risk of errors and fraud in cash transactions. With strong internal controls, Toko Roti Raos can improve operational effectiveness and ensure that the data recorded in the accounting information system remains accurate and trustworthy, which in turn can enhance financial performance and facilitate more informed decision-making.